User Satisfaction Level of The SiCepat Proof of Delivery Website Using The Pieces Framework Method - Priatno; Sudrajat, Dearsalva; Effendi, Muhammad Ridwan (Jurnal Teknologi Informatika dan Komputer, 2025)
Information technology and online platforms are very important in the context of work in today's digital era. Many companies have turned to internal websites or web-based systems for various needs, such as data management, internal communications, and daily work tools. One technology that is considered to play a very important role in a company is a website. SiCepat Ekspres implemented the Proof Of Delivery website as a solution to solving problems that occur when sending goods to user receipts. This system is part of the company's digital strategy, which utilizes website-based technology to simplify operations and increase user satisfaction. The data collection methods in this thesis are observation, interviews and literature study methods with quantitative analysis methods, namely data analysis methods using statistical analysis. Satisfaction with using a website is formed because of the services provided by a system that can be adjusted to the user's wishes. One method that can be used to analyze website systems is the PIECES Framework where there are 6 indicators (Performance, Information, Economy, Control, Efficiency, and Service) by distributing questionnaires to employees of the Head Office of the Operations Division, getting 60 respondents. The results of this research show that the Proof Of Delivery SiCepat website received an average score of 4.30 which shows that users are very satisfied in using the Proof Of Delivery SiCepat website as a media source of information.